Effects of saccadic eye movements on postural control stabilization - Rodrigues, Sérgio Tosi [UNESP]; Aguiar, Stefane Aline; Polastri, Paula Fávaro [UNESP]; Godoi, Daniela; Moraes, Renato; Barela, Jose Angelo [UNESP] (Universidade Estadual Paulista (Unesp), Instituto de Biociências, 2013)
Several structures of the central nervous system share involvement in both ocular and postural control, but the visual mechanisms in postural control are still unclear. There are discrepant evidences on whether saccades would improve or deteriorate stabilization of posture. The purpose of this study was to determine the influence of saccadic eye movements on postural control while standing in different basis of support. Twelve young adults stood upright in wide and narrow stances while performing fixation and saccades of low and high frequencies. Body sway was attenuated during saccades. Trunk anterior-posterior sway and trunk total displacement decreased during saccades compared to fixation; higher sway mean frequency in anterior-posterior direction during saccades was observed. Body sway was reduced in wide compared to narrow stance during high frequency saccades. These results indicate that eye movement improves postural stabilization and this effect is stronger in combination of wide stance-high frequency gaze condition.

Várias estruturas do sistema nervoso central compartilham envolvimento nos controles ocular e postural, mas os mecanismos visuais no controle postural ainda não estão claros. Existem evidências discrepantes sobre a possibilidade de movimentos sacádicos melhorarem ou deteriorarem a estabilização postural. O objetivo desse estudo foi determinar a influência de movimentos sacádicos dos olhos sobre o controle postural em diferentes bases de apoio. Doze adultos jovens ficaram em pé, mantendo a postura sobre base ampla e restrita enquanto realizavam fixações e movimentos sacádicos de baixa e alta frequência. Oscilação corporal foi atenuada durante movimentos sacádicos. A oscilação do tronco na direção ântero-posterior e o deslocamento total do tronco diminuíram durante movimentos sacádicos comparados à fixação; maior frequência média de oscilação na direção ântero-posterior durante movimentos sacádicos também foi observada. Oscilação corporal foi reduzida em postura com base ampla comparada à restrita durante movimentos sacádicos de alta frequência. Estes resultados indicam que o movimento do olho melhora a estabilização postural e este efeito é mais forte na condição que combina base ampla e alta frequência do olhar.
Efeitos dos movimentos sacádicos oculares na estabilização do controle postural
Efectos de los movimientos sacádicos oculares en la estabilización de control postural
Keywords: saccades; eye movements; posture